Isolation and characterization of an exopolygalacturonase from Fusarium oxysporum f.sp. cubense race 1 and race 4 - Dong, Zhangyong (BioMed Central, 2011)
BACKGROUND: Fusarium wilt is an economically devastating disease that affects banana production. Although Cavendish banana cultivars are resistant to Fusarium oxysporum f.sp. cubense race 1 (FOC1) and maitain banana production after Gros Michel was destructed by race 1, a new race race 4 (FOC4) was found to infect Cavendish. RESULTS: An exopolygalacturonase (PGC2) was isolated and purified from the supernatant of the plant pathogen Fusarium oxysporum f.sp. cubense race 4 (FOC4). PGC2 had an apparent Mr of 63 kDa by SDS-PAGE and 51.7 kDa by mass spectrometry. The enzyme was N-glycosylated. PGC2 hydrolyzed polygalacturonic acid in an exo-manner, as demonstrated by analysis of degradation products. To obtain adequate amounts of protein for functional studies between the PGC2 proteins of two races of the pathogen, pgc2 genes encoding PGC2 from race 4 (FOC4) and race 1 (FOC1), both 1395 bp in length and encoding 465 amino acids with a predicted amino-terminal signal sequence of 18 residues, were cloned into the expression vector pPICZaA and then expressed in Pichia pastoris strains of SMD1168. The recombinant PGC2 products, r-FOC1-PGC2 and r-FOC4-PGC2, were expressed and purified as active extracellular proteins. Optimal PGC2 activity was observed at 50°C and pH 5. The K(m )and V(max )values of purified r-FOC1-PGC2 were 0.43 mg.mL(-1 )and 94.34 units mg protein(-1 )min(-1), respectively. The K(m )and V(max )values of purified r-FOC4-PGC2 were 0.48 mg.mL(-1 )and 95.24 units mg protein(-1 )min(-1), respectively. Both recombinant PGC2 proteins could induce tissue maceration and necrosis in banana plants. CONCLUSIONS: Collectively, these results suggest that PGC2 is the first exoPG reported from the pathogen FOC, and we have shown that fully functional PGC2 can be produced in the P. pastoris expression system.